Well‐Defined Copper(I) Fluoroalkoxide Complexes for Trifluoroethoxylation of Aryl and Heteroaryl Bromides1. (17th March 2015) - Huang, Ronglu; Huang, Yangjie; Lin, Xiaoxi; Rong, Mingguang; Weng, Zhiqiang
Abstract Copper(I) fluoroalkoxide complexes bearing dinitrogen ligands were synthesized and the structure and reactivity of the complexes toward trifluoroethoxylation, pentafluoropropoxylation, and tetrafluoropropoxylation of aryl and heteroaryl bromides were investigated.